Stress Tests and Liquidity Crisis in the Banking System - Llorent, Julián; Melgar, María del Carmen; Ordaz, José Antonio; Guerrero, Flor María (Equilibrium. Equilibrium. Quarterly Journal of Economics and Economic Policy, 2013)
The paper´s aim is to contribute to the debate on the impact of stress test on banking system liquidity. Due to the theoretical character of the problem, the used methodology is a set of results from research and theoretical works about how the attempts to increase system solvency could lead into a greater lack of liquidity.